Effect of Topical Atropine on Wound Contraction in Swiss Albino Mice : A preliminary report - P Kumar; G C Jagetia (Indian Journal of Plastic Surgery)
The influence of topical application of atropine ointment was studied in artificially wounded Swiss albino mice. Full thickness excision wounds were made surgically on the dorsum of mice. One mm thick layer of atropine ointment was applied topically on the whole area of wound daily, till the healing of wound. The topical application of atropine ointment significantly delayed the contraction of wound in the atropine treated group when compared with the untreated controls. There was a significant delay in the mean wound healing time (HTM) in the atropine treated group when compared to untreated control group.